Epidemiological characteristics and factors affecting healing in unintentional pediatric wounds - Gao, Hua; Li, Yang; Jin, Shaobin; Zhai, Wenli; Gao, Yanhua; Pu, Linzhe (Frontiers in Public Health, 2024)
Objective: To analyze the epidemiological characteristics and wound healing conditions of common unintentional skin lacerations in children. Methods: A retrospective analysis was conducted on data from 1,107 children, aged 0-12 years, with skin lacerations who received emergency treatment at Qilu Hospital of Shandong University from January 1, 2019, to December 30, 2022. Data on age, injury site, time from injury to suturing, and wound healing conditions were statistically analyzed. Results: Among the 1,107 cases, 714 (64.5%) were male and 393 (35.5%) were female, with a male-to-female ratio of 1.8:1; median age was 5 years (IQR, 3-7). Infants and toddlers (0-3 years old) constituted the highest proportion, accounting for 36.3% (402 cases). The number of children aged over 3 years gradually decreased with increasing age. In younger children, the most common injuries were to the forehead, scalp, and lower jaw; in school-aged children, the proportion of limb and trunk injuries significantly increased. Age (OR, 1.34; 95% CI, 1.23 - 1.46), outdoor injuries (OR, 2.21; 95% CI, 1.18 - 4.16), lower limb injuries (OR, 5.35; 95% CI, 2.86 - 10.00), and wound length greater than 3 cm (OR, 10.65; 95% CI, 5.02 - 22.60) were significant risk factors for poor wound healing. The risk of poor wound healing increased by 34% for each additional year of age. Conclusion: In children, the common sites of unintentional skin lacerations show distinct age and gender distribution characteristics. Older age, outdoor injuries, longer wound lengths, and lower limb injuries are independent risk factors for poor wound healing.